Les albums utilisés avec les élèves : approche quantitative des choix différenciés des enseignants de cycle 3 - Stéphane Bonnéry; Jacques Crinon; Brigitte Marin (Recherches en Éducation)
This article which is based on a research questionnaire (n=281) shows that which stays or changes at the end of primary school in comparison to the lower school levels equally depends on the choices of reading that the teachers make for their pupils. More specifically, in a sociological approach, we analyze the differences in the contexts (in all Educational Areas – priority or not) to understand the different choices of books that teachers make. The investigation involved a refined analysis (quantitative level and qualitative analysis of each book) to study the sociological breakdown of the use of books that may appear easy or difficult for the different classes at the end of primary school.